UMBI UBI JALAR UNGU BALI (Ipomoea batatas) DI TRANSAMINASE SERUM, MALONDIALDEHIDE HEPAR DAN ALKOHOL KRONIS - I Wayan Putu Sutirta-Yasa; I Made Jawi; Ida Bagus Ngurah; Anak Agung Ngurah Subawa (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Oxidative stress as a consequence of chronic alcoholic intake causes lesions of liver tissue. The objective of this study was to identifythe antioxidant effect of ethanol extract derived from Balinese purple sweet potato on the liver tissue in mice after chronic consumptionof alcohol. Subjects of this study were 32 adults male Swiss mice (12–14 weeks) divided into 4 groups with control group post-testonly design. Post-treatment of blood and liver samples were collected from each group of 8 mice. The MDA liver was quantified withthiobarbituric acid reactive substances (TBARS) method. Samples were collected from control group of 8 mice without sweet potatoextract and alcohol, 8 mice with 1 mg extract of Balinese purple sweet potato, 8 mice with 0.8 gram alcohol, and 8 mice with combineof alcohol and extract of Balinese purple sweet potato, each treatment was carried out every day for 4 weeks. The results showed asignificant increase of serum SGOT, SGPT and liver MDA level, after chronic consumption of alcohol (p = 0.00). The decrease of serumSGOT, SGPT and liver level MDA was significant in the group with extract of Balinese purple sweet potato (p = 0.00). The researchersconcluded that the extract of Balinese purple sweet potato had an antioxidant effect in mice which consumed alcohol chronically. Basedon this study it is concluded that extract of Balinese purple sweet potato has a protective effect on the liver cell in mice which consumedalcohol chronically.